A New Era of Extended Time Window Acute Stroke Interventions Guided by Imaging. (January 2020) - Rehani, Bhavya; Ammanuel, Simon G.; Zhang, Yi; Smith, Wade; Cooke, Daniel L.; Hetts, Steven W.; Josephson, S. Andrew; Kim, Anthony; Hemphill, J. Claude; Dillon, William
Ischemic stroke is one of the most debilitating and deadliest conditions worldwide. Intravenous t-PA is the current standard treatment within 4 hours after onset of symptoms. Recent randomized controlled trials have demonstrated the efficacy of neurointerventional intra-arterial treatment in acute ischemic stroke. About 20% of acute ischemic stroke are classified as wake-up strokes, which falls out of the conventional treatment time window. New evidence suggests that some patients with longer time from symptom onset (up to 24 hours) may benefit from thrombectomy, probably in part due to variations in collateral circulation among individual patients. Advanced imaging can play a crucial role in identifying patients who could benefit from endovascular intervention presenting within extended treatment time windows. In this article, we review the advanced imaging algorithm for ischemic stroke workup in the multiple studies published to date and summarize the results of the clinical trials for late ischemic stroke that can be clinically useful.